Body of Evidence in Favor of Adopting 130/80 mm Hg as New Blood Pressure Cut-Off for All the Hypertensive Disorders of Pregnancy - Giovanni Sisti; Belinda Williams (Medicina, 2019)
The American College of Cardiology/American Heart Association (ACC/AHA) updated its guideline redefining the classification of hypertension and the blood pressure cut-off in 2017. The current cut-offs for stage 1 hypertension of 130 mm Hg systolic blood pressure or 80 mm Hg diastolic blood pressure replace the previous cut-offs of 140 mm Hg systolic blood pressure or 90 mm Hg diastolic blood pressure which were based on the ACC/AHA guidelines from 1988. However, the blood pressure cut-off for the obstetric population still remains as 140/90 mm Hg despite the scarcity of evidence for it. Recent American College of Obstetricians and Gynecologists (ACOG) bulletins for pregnant women have not reflected the new ACC/AHA change of guideline. We reviewed a mounting body of evidence prompting the implementation of the new ACC/AHA guidelines for the obstetric population. These studies examined maternal and fetal outcomes applying the new ACC/AHA guidelines during antepartum or postpartum care.